Konsep Keadilan Politik Dalam Menegakkan Hukum Islam - Ardiyanti (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
Allah SWT commands all Muslims to do justice to others without discriminating between one group and another. Al-'adl is one of the Asmaul Husna or 99 names (attributes) of Allah which means Allah is Just. This study aims to determine the concept of Al-'adl in Islam through Islamic figures and philosophers. The research uses an approach. The method used in this study is library research, because the data sources are from books, journals and other written documents. The results of the study indicate that the concept of justice is the concept of political justice in enforcing Islamic law and is an order from Allah SWT that must be carried out for all Muslims. it is supported by Islamic leaders who always uphold the attitude of justice, especially for leaders as expressed by Al-Ghazali, Ibn Taimiyah and Ibn Kahldun. The three figures agreed in conceptualizing political justice in upholding Islamic law, which is aimed at the welfare of the community.